Biotin-Responsive Ophthalmoplegia / Dystonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
A 10-year-old girl with a 4-month history of abnormal gait and dysarthria had bilateral external ophthalmoplegia, dystonia, and altered mental status.